Management Strategies for Double-Crop Soybean Planted After Wheat - D. S. S. Hansel; J. Kimball; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
Double-crop (DC) soybeans (Glycine maxL.) are gaining popularity as an alternative system to intensify productivity without expanding the farming area and can potentially increase net return. However, the DC soybean system faces many challenges such as late planting, which decreases yield potential. A study was conducted in four site-years in Ashland Bottoms, KS, during the 2016 and 2017 growing seasons. In both years, the soybean variety planted was Asgrow 4232 (MG 4.2). The soybean was planted right after two different wheat harvest timings (Study 1, early-wheat harvest 18–20% moisture; and Study 2, conventional-harvest 13–14% moisture). Seven treatments were evaluated in each of the soybean planting dates: 1) common practice; 2) no seed treatment (without seed fungicide + insecticide treatment); 3) non-stay green (without foliar fungicide + insecticide application); 4) high seeding rate (180,000 seeds/a); 5) wide rows (30-inch row-spacing); 6) nitrogen (N) fixation (without late-fertilizer N application); and 7) kitchen sink (includes all management practices). There was adequate precipitation distribution in 2016, which helped to nurture the soybean plants even when planting later in the season. In 2017, precipitation was not well distributed, and the early planting date was affected by low precipitation during early season. Overall, the high plant population and the kitchen sink treatments presented maximum yields, while the common practice scenario showed the lowest yields.
Keywords: soybean; improve yield; intensive management